Self‐Assembly Core–Shell Graphene‐Bridged Hollow MXenes Spheres 3D Foam with Ultrahigh Specific EM Absorption Performance. (22nd August 2018) - Li, Xinliang; Yin, Xiaowei; Song, Changqing; Han, Meikang; Xu, Hailong; Duan, Wenyan; Cheng, Laifei; Zhang, Litong
Abstract: Electromagnetic wave (EM) absorption materials with broader effective absorption bandwidth (EAB), lightweight, and thinness characteristics are highly desirable in areas of wearable device and portable electronics. However, there are still many obstacles to simultaneously satisfy the above critical requirements required by new high‐performance EM absorption materials. Herein, for the first time, Ti3 C2 T X MXenes are selected as the dielectric mediator to prepare reduced graphene oxide (RGO)/Ti3 C2 T X hybrids foam with hollow core–shell architectures and controllable complex permittivity via self‐assembly and sacrificial template processes, under the guidance of theoretical calculations. RGO is grafted flatly on the outer surface of the Ti3 C2 T X spheres‐core, forming a unique heterostructure. The RGO/Ti3 C2 T X foam possesses excellent EM absorption performance superior to all reported foam‐based counterparts, the EAB covers the whole X‐band at 3.2 mm while the density is merely 0.0033 g cm −3, and its specific EM absorption performance ( SMAP = RL (dB)/ Thickness (cm)/ Density (g cm −3 )) value exceeds 14 299.2 dB cm −2 g −1, verifying the above theoretical results. This study is expected to guide future exploration on designing high‐performance EM absorption materials, and the RGO/Ti3 C2 T X foam can be promising candidates in energy storage, sensors, and wearable electronics fields. Abstract : The dynamic relationship between the complex permittivity and thickness is calculated and proven by selecting Ti3 C2 T X MXenes spheres as the dielectric mediator for the first time. The resulting 3D ultralight RGO/Ti3 C2 T X foam with hollow core–shell architectures exhibits excellent specific electromagnetic wave (EM) absorption performance value (>14299.2 dB cm −2 g −1 ), providing a novel model for preparing high‐performance EM absorption materials.